Performance evaluation of 10~MW grid connected solar photovoltaic power plant in India - B. Shiva Kumar; K. Sudhakar (Energy Reports, 2015)
The growing energy demand in developing nations has triggered the issue of energy security. This has made essential to utilize the untapped potential of renewable resources. Grid connected PV systems have become the best alternatives in renewable energy at large scale. Performance analysis of these grid connected plants could help in designing, operating and maintenance of new grid connected systems. A 10~MW photovoltaic grid connected power plant commissioned at Ramagundam is one of the largest solar power plants with the site receiving a good average solar radiation of 4.97~kW~h/m2/day and annual average temperature of about 27.3 degrees centigrade. The plant is designed to operate with a seasonal tilt. In this study the solar PV plant design aspects along with its annual performance is elaborated. The various types of power losses (temperature, internal network, power electronics, grid connected etc.) and performance ratio are also calculated. The performance results of the plant are also compared with the simulation values obtained from PV syst and PV-GIS software. The final yield (Y F) of plant ranged from 1.96 to 5.07~h/d, and annual performance ratio (PR) of 86.12%. It has 17.68% CUF with annual energy generation of 15798.192~MW~h/Annum.
Keywords: 330; Performance ratio; Photovoltaic; PV syst software; SCADA system; SolarGIS-pvplanner